Electric Bikes in North America: Results of an Online Survey. Issue 1 (January 2014) - MacArthur, John; Dill, Jennifer; Person, Mark
The research described in this paper was conducted in part to understand whether different bicycling technology–-in this case, electric-assist bicycles (e-bikes)–-could reduce barriers to bicycling such as trip distance, topography, time, and rider effort. If so, this technology may result in more bike trips and longer bike trips and may increase the diversity of people bicycling, including people with disabilities or chronic injuries. An e-bike typically resembles a standard pedal bicycle with the addition of a rechargeable battery and electric motor to assist with propulsion. To address these aims, an online survey was conducted of existing e-bike users, who were surveyed about their purchase and use decisions. Responses from 553 e-bike users across North America were analyzed. Results suggest that e-bikes enable users to bike more often, to travel longer distances, and to carry more cargo with them. Additionally, e-bikes allow people who otherwise would not be able to bike (because of physical limitations or proximity to locations) the ability to bike with electric assist.